(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
Key words: Ibuprofen; Dissolution rate; solid dispersion; fusion method; Kollidone; Povidone DOI: http://dx.doi.org/10.3329/sjps.v3i2.8030 S.J. Pharm. Sci 3(2): 07-11